Priorities for completing the European Union's Single Market - Stráský, Jan (OECD Publishing, 2016)
The EU Single Market remains far from completed: progress in goods and services market integration has stalled, financial markets are still fragmented along national lines and the barriers to labour mobility remain high. Restrictive regulation within countries and regulatory heterogeneity across them hamper the internal market, reducing trade and investment flows. Network sectors, such as energy and transportation, are insufficiently interconnected and open to competition, and inefficient as a result. Reinvigorating the single market is one of the key tools to strengthen the recovery of the European Union and restore faster growth of income per capita. To support the recovery, structural reforms that yield short-run as well as long-run gains should be prioritised. Policies enhancing labour and capital mobility are especially relevant, as they provide channels of adjustment to country-specific shocks and reinforce the effectiveness of stabilisation policies. Policies enhancing capital mobility include improved securitisation, better collection and sharing of credit information regarding smaller firms and the convergence of insolvency regimes. Labour mobility within the European Union would profit from reduced administrative and regulatory burden, such as faster recognition of professional qualifications and better portability of social and pension rights. Product markets reforms also have the potential to deliver benefits swiftly, not least by unlocking investment. Regulatory burdens could be alleviated by better impact assessment for legislative proposals and ex post evaluation of policies. Product market reforms in network sectors should include harmonisation of regulations and technical specifications, with the target of establishing single EU regulators. This Working Paper relates to the 2016 OECD Economic Survey of the European Union (www.oecd.org/eco/surveys/economic-survey-european-union-and-euro-area.htm)
Keywords: Economics